Cancer prevention in people experiencing homelessness: ethical considerations and experiences from the CANCERLESS project - Coronado-Vázquez, María del Valle; Gómez-Trenado, Rosa; Benito-Sánchez, Beatriz; Barrio-Cortes, Jaime; Gil-Salmerón, Alejandro; Amengual-Pliego, Miguel; Grabovac, Igor (Frontiers in Public Health, 2024)
The incidence of cancer in Europe has been increasing in recent years. Despite this, cancer prevention has remained a low priority in health policies. Cancer is one of the main causes of mortality among people experiencing homelessness, who continue to have difficulties accessing prevention programs. A strategy that has been tested to favor cancer prevention is the health navigator figure. The objective of CANCERLESS project is to implement this model among populations experiencing homelessness in four European countries to foster the prevention and early detection of cancer. In this perspective, a presentation of CANCERLESS project is made, and its ethical aspects are discussed according to the ethics of public health, the ethics of care, solidarity, relational autonomy, and the social recognition of the virtue of just generosity. The ethical foundations of CANCERLESS project are rooted in social justice and in equity in access to health systems in general and cancer screening programs in particular. The ethics of public health guided by utilitarianism are insufficient in serving the interests of the most disadvantaged groups of the population. Hence, it is necessary to resort to relational bioethics that includes the ethics of care and solidarity and that recognizes the moral identity of socially excluded persons, reaffirming their position of equality in society. Relational autonomy therefore provides a broader conception by including the influence of living conditions in decisions. For this reason, the CANCERLESS project opts for a dialogue with those affected to incorporate their preferences and values into decisions about cancer prevention.